The Fall, 1969 Guidance Examination A Report on Some Proposed New Tests - Gold, Ben K.; Los Angeles City Coll., CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
Test performance statistics and subsequent academic achievement data for Los Angeles City College (LACC), California, students entering in the fall of 1969 are reported in this study. The test performance statistics provide a relative comparison between achievement on the School and College Ability Test (SCAT), the Form 1A Reading Comprehension: Cooperative Reading Test (reading and vocabulary), and an essay constructed by members of the LACC English Department. Data are arrayed in terms of both the entire test population and sub-groups of males, females, students from predominantly Black high schools, and students from foreign high schools. Observations concerning performance by individual sub-groups are included, along with correlation findings of .63, .88, and .79 between the SCAT, and the essay, vocabulary, and reading tests respectively. Subsequent studies will report on examinations (excluding SCAT) given in the spring of 1970, along with attempts to measure student opinion of the examination procedure. [Not available in hard copy due to marginal legibility of original document.] (JO)
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Ability; Guidance Programs; Institutional Research; Comparative Testing; Educational Testing; Statistical Surveys; Student Placement; Two Year Colleges; Cooperative Reading Comprehension Tests -- School and College Ability Tests; California